Website Quality Evaluation Based on Search Engine Queries using Web Rank Position Algorithm (WRPA) - Chandran M; Ramani A. V (Institute of Advanced Engineering and Science, 2016)
The research work is about to test the quality of the website and to improve the quality by analyzing the hit counts, impressions, clicks, count through rates and average positions. This is accomplished using WRPA and SEO technique. The quality of the website mainly lies on the keywords which are present in it. The keywords can be of a search query which is typed by the users in the search engines and based on these keywords, the websites are displayed in the search results. This research work concentrates on bringing the particular websites to the first of the search result in the search engine. The website chosen for research is SRKV. The research work is carried out by creating an index array of Meta tags. This array will hold all the Meta tags. All the search keywords for the website from the users are stored in another array. The index array is matched and compared with the search keywords array. From this, hit to count is calculated for the analysis. Now the calculated hit count and the searched keywords will be analyzed to improve the performance of the website. The matched special keywords from the above comparison are included in the Meta tag to improve the performance of the website. Again all the Meta tags and newly specified keywords in the index array are matched with the SEO keywords. If this matches, then the matched keyword will be stored for improving the quality of the website. Metrics such as impressions, clicks, CTR, average positions are also measured along with the hit counts. The research is carried out under different types of browsers and different types of platforms. Queries about the website from different countries are also measured. In conclusion, if the number of the clicks for the website is more than the average number of clicks, then the quality of the website is good. This research helps in improvising the keywords using WRPA and SEO and thereby improves the quality of the website easily.